A Descriptive Correlational Study of Parental and Adolescents Religiosity Practices with Adolescent Sexual Behavior - Suazini, Esa Risi; Humaeroh, Lina; Hidayat, Fajarini Putri; Huda, Taufik (JURNAL KEBIDANAN, 2025)
Indonesia is the 7th most religious country in the world, with a majority Muslim population. Research revealed that 22.6% of teenagers engaged in risky sexual behavior, leading to pregnancies that may result in severe health complications or even fatalities. Parents play a very important role in this phenomenon. The purpose of this study was to determine the description and influence of parental and adolescent religiosity on adolescent sexual behavior. Religiosity is discussed based on the teachings of Islam. This type of research method was descriptive correlation. The sample collection technique combines incidentally and snowball techniques. Adolescents and parents who have filled out the questionnaire redistribute it to fellow adolescents who meet the inclusion criteria (adolescent age 10-18 years old, not married, adolescents and parents had the same religion, namely Islam and were willing to be respondents). Data analysis using SmartPLS 3. The sample consisted of 97 adolescents aged 10-18 years and 97 parents. There is a strong, positive and stastitically significant influence of parental religiosity on adolescent religiosity (R2: 0.315, path coefficient 0.561, t-value: 7.984, and p-value 0.000). Second, there is a low, but statistically significant negative influence of adolescent religiosity on adolescent sexual behavior (R2: 0.193, path coefficient -0.440, t-value: 6.592, p-value 0.000). Parental religiosity makes a large contribution to variations in adolescent religiosity (f2: 0.460) and adolescent religiosity makes a moderate contribution to variations in adolescent sexual behavior (f2: 0.240). It is important for parents to instill the values of religiosity to their children so that they can fortify themselves from free sexual behavior.